Assessment of rapid diagnostic tests and fourth‐generation Enzyme‐Linked Immunosorbent Assays in the screening of Human Immunodeficiency and Hepatitis B virus infections among first‐time blood donors in Libreville (Gabon) - Eko Mba, Jean Marie (J Clin Lab Anal, 2018)
BACKGROUND: Blood transfusion is a pathway for the transmission of blood‐borne pathogens such as human immunodeficiency virus (HIV) and hepatitis B virus (HBV) from donors to recipients in most countries in sub‐Saharan Africa, including Gabon. The study aimed to compare the performance of four rapid diagnostic tests (RDTs: Alere DETERMINE, BIOSYNEX Exacto Pro HIV, MEDIFF HIV 1&2, and BIOSYNEX IMMUNOQUICK HBsAg) with results of 4th‐generation immunoenzymatic assays COBAS 6000 e601 and EVOLIS BioRad for the detection of HIV and hepatitis B surface antigen (HBsAg) in blood donors in Libreville, Gabon. METHODS: Reactive and nonreactive blood samples for HIV and HBsAg were selected using fourth‐generation ELISA COBAS 6000 e601 and EVOLIS BioRad. The sensitivities of RDTs were calculated using Epi Info version 6.04dfr (CDC, Atlanta, USA). RESULTS: Sensitivities for the detection of HIV in blood donors were 90.9% for Alere DETERMINE, 81.8% for BIOSYNEX Exacto Pro HIV, and 81.8% for MEDIFF HIV 1&2 Serum/sang Total Cassette compared with COBAS 6000 e601. The sensitivity of Alere DETERMINE compared to the semi‐automated ELISA Bio‐Rad for HIV detection was 65.6%. The sensitivity of BIOSYNEX IMMUNOQUICK HBsAg compared to ELISA tests for the detection of HBsAg was 78.0%. The specificity of all RDTs for the detection of HIV and HBsAg was 100%. CONCLUSION: Alere DETERMINE HIV‐1/2, MEDIFF HIV 1&2 Serum/sang Total Cassette, BIOSYNEX Exacto Pro HIV, and BIOSYNEX IMMUNOQUICK HBsAg are not recommended for determining whether donors qualify to donate blood because of their low sensitivity for the detection of HIV antibodies and HBsAg in blood donors in Gabon.